Kontribusi dan Efektivitas Pajak Daerah Di Kabupaten Sumba Timur - Renggo, Yuniarti Reny (JURNAL EKONOMIKA, 2024)
This research was conducted in East Sumba Regency which is one of the regencies of East Nusa Tenggara Province. This research aimed to see the contribution and effectiveness of regional taxes in increasing local income of regency (PAD). The data analysis method used was secondary data with descriptive quantitative data analysis methods, since 2014 to 2022. Regional taxes in East Sumba Regency experienced fluctuations from 2014 - 2022, and the fluctuations were only between the criteria of less and moderate in contributing of increasing regional income. Even though it was still in the moderate criteria, local taxes were still quite effective in increasing income. The results obtained that the effectiveness of local taxes had fluctuated, where since 2014 - 2016 it was classified as very effective. However, in 2017 - 2021 it continued to fluctuate until in 2022 where it decreased to be quite effective. This became feedbacks for the region to increase regional income